Elementary statistics - Hoel, Paul Gerhard (New York : John Wiley & Sons, 1971)
This book is designed for a one semester course for the student whose background in mathematics is limited to high school algebra.
Includes index.
rpm 25/07/2018
Loans
Keywords: Statistics